Application of Remote Sensing Technology in Heat Island Effect of Major Cities in Fujian Province - Lin, Zijun (Transactions on Environment, Energy and Earth Sciences, 2024)
Remote sensing technology has many advantages for the investigation of the urban heat island (UHI) effect. Firstly, remote sensing technology is real-time and dynamic, which can monitor the change of environment in real-time. Secondly, remote sensing technology has low cost and high efficiency, which saves a lot of manpower and material costs. Finally, remote sensing technology has accuracy and reliability, which provides scientific basis for environmental monitoring. Focusing on the UHI in Fujian Province, this paper introduces the data, sources and methods of remote sensing technology, and discusses the features and determinants of the UHI effect in Pingtan Island, Xiamen City and Fuzhou City. In the evaluation of land surface temperature (LST), the remote sensing image data of Landsat5 and Landsat8 are obtained firstly, and LST inversion method is used to obtain. It is found that underlying surface properties are changed by human activities, such as reclamation activities and changes in land use types, increases the mean surface temperature in Fuzhou, Xiamen and Pingtan Island, which intensifies the UHI effect. Based on the research review, relevant suggestions are put forward for city managers. In the process of urbanization, city managers should pay attention to the economy and ecology development, and take relevant measures, such as increasing the urban green space, optimizing the layout of green space, improving the property of urban underlying surface, and improving the surface reflectivity, to alleviate the UHI effect.